O04.4 Seroprevalence of Herpes Simplex Virus Types 1 and 2 United States, 1999–2010. (13th July 2013) - Bradley, H; Markowitz, L E; Gibson, T; McQuillan, G M
Abstract : Background: Herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) are common infections with serious sequelae. HSV-1 is an increasingly important cause of genital herpes in industrialised countries, potentially due to less acquisition of HSV-1 during childhood or to changes in sexual behaviour. Methods: Using nationally representative data from the National Health and Nutrition Examination Surveys (NHANES), we examined change in seroprevalence of HSV-1 and HSV-2 among 14–49 year olds in the United States. We compared seroprevalence in 1999–2004 with 2005–2010, and examined seroprevalence among 14–19 and 20–29 year-olds stratified by socio-demographic characteristics and sexual behaviours. We also reviewed HSV-1 and HSV-2 seroprevalence from 1976–1980 to 2005–2010. Results: In 2005–2010, the seroprevalence of HSV-1 was 53.9%, and the seroprevalence of HSV-2 was 15.7%. From 1999–2004 to 2005–2010, HSV-1 seroprevalence declined by nearly 7% (P < 0.01), but HSV-2 seroprevalence did not change significantly. The largest decline in HSV-1 seroprevalence from 1999–2004 to 2005–2010 was observed among 14–19 year olds, among whom seroprevalence declined by nearly 23%, from 39.0% to 30.1% (P < 0.01). In this age group, HSV-1 seroprevalence declined among young men and women, non-Hispanic blacks and whites, and those living above and below the federal poverty level. Overall, HSV-1 seroprevalence declined more than 10% from 60.1% in 1976–1980 to 53.9% in 2005–2010 (P < 0.01). Among 14–19 year olds, HSV-1 seroprevalence declined more than 29%, from 42.6% to 30.1% (P < 0.01). Overall, HSV-2 seroprevalence increased slightly from 13.4% in 1976–1980 to 15.7% in 2005–2010 (P = 0.02). Conclusions: An increasing number of adolescents lack HSV-1 antibodies at sexual debut and are susceptible to genital HSV-1 infection. In the absence of declines in HSV-2 infections, the prevalence of genital herpes may increase.